(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the effects of the inclusion of crude glycerin containing 80.5% glycerol on the blood parameters of lambs in confinement. 39 crossbred lambs, without a defined breed standard, non-castrated males, with four months of age and initial body weight of 21 kg ± 0.8 kg, were distributed in randomized blocks with four treatments and ten repetitions with levels of inclusion of 0, 6, 12 and 18% crude glycerin in the dry matter (DM) of the diet. Blood samples were taken to analyze different biomarkers on the 650 day of the experiment. There were no significant effects of the inclusion of crude glycerin to replace corn in the lambs diet in relation to the different biomarkers of the protein, mineral and enzymatic activity. Regarding the energy profile, a significant effect was identified only for the plasma glucose concentration (p=0.0003). In the regression analysis of the plasma glucose concentration of lambs, depending on the level of consumption of crude glycerin associated with urea to replace corn, it was found that the greater the inclusion of crude glycerin in the diet, the greater the blood glucose (r=0,92; p<0001). The increasing amount of crude glycerin in the diet of lambs growing to replace corn has a gluconeogenic character, in addition to that it does not cause metabolic alteration of parameters related to the energy, protein, mineral and enzymatic activity profile. Crude glycerin can be supplied up to 18% for promoting an adequate metabolic response.